School Leadership Development and Arts-Based Pedagogical Practices in a University in South Korea - Lu, Jing (Pacific International Journal, 2025)
This study examines the influence of school leadership development programs on arts-based pedagogical practices among art and design faculty at a university in South Korea. Leadership training in arts and design management equips educators with skills to integrate creative, administrative, and instructional strategies, fostering innovation in teaching. Findings indicate that such programs enhance teachers’ abilities in curriculum design, technology integration, interdisciplinary collaboration, and reflective practice. However, challenges such as resource limitations and resistance to change persist. The research underscores the importance of tailored leadership development in promoting effective, culturally responsive arts education.